Studies of Y-chromosome Polymorphism in the Context of History: Current State of the Discipline » - Zh.M. Sabitov (Золотоордынское обозрение)
Polymorphism of Y-chromosome is an interdisciplinary science which aims to answer historical questions related to the peoples’ ethnogenesis on the basis of population genetic research . Scientific research of Y-chromosome polymorphism began at the end of 1990s. Studies of Y-chromosome polymorphism represent only part of population genetic researches. In 2002 there was introduced a single standard regarding SNP-tree mutations and names haplogroups (consortium of Y-chromosome). Prior to this there was no less than 5 different classifications haplogroups. About this time, the National Genographic Project have been started, which purpose was to explore all the world populations by STR (short tandem repeats) and SNP (single nucleotide polymorphism) mutations of Y-chromosome. The basis is the principle of geographical residence. The results of research of the participants of this project resulted in hundreds of articles on the ethnogenesis of different nations of the earth published in journals specialized in population genetics, mainly in the English. In this article, the author presents his view on the methodological problems related to establishing of new application of historical science (the study of polymorphism of the Y-chromosome). The article contains descriptions and examples of faulty research and methodological mistakes. The author also addressed the issue of historiography of the study of the ethnogenesis of the Turkic peoples of Eurasia and methods of population genetics identifying the tools and methods for the study of Y-chromosome polymorphism. This article describes the methods of population genetics such as cluster analysis, phylogenetic networks, multidimensional scaling, calculation of “genetic” distances, TMRCA.